2001
DOI: 10.1101/gad.195101
|View full text |Cite
|
Sign up to set email alerts
|

Two enhancers and one silencer located in the introns of regA control somatic cell differentiation in Volvox carteri

Abstract: The regA gene plays a central role in germ-soma differentiation of Volvox carteri by suppressing all reproductive functions in somatic cells. Here we show that the minimal promoter of regA consists of only 42 bp immediately upstream of the transcription start site, and that it contains no discernible regulatory elements. However, introns 3 and 5 are both required for regA expression in somatic cells, and intron 7 is essential for silencing regA in gonidia (asexual reproductive cells). A regA gene lacking intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
1
34
0
1
Order By: Relevance
“…In regA (somatic regenerator) mutants, somatic cells form normally after embryogenesis, but then redifferentiate into gonidia; they withdraw their flagella, grow, and subsequently divide into new embryos (Starr 1970;Huskey and Griffin 1979). regA is a nuclear protein that is related to transcriptional repressors and expressed in somatic cells and required to maintain their fate Stark et al 2001). regA belongs to a family of VARL (Volvocine algae regA-like) proteins with 14 members in Volvox and 12 in Chlamydomonas (Duncan et al 2006(Duncan et al , 2007.…”
Section: Multicellular Innovations In the Volvocine Lineage Are Modifmentioning
confidence: 99%
“…In regA (somatic regenerator) mutants, somatic cells form normally after embryogenesis, but then redifferentiate into gonidia; they withdraw their flagella, grow, and subsequently divide into new embryos (Starr 1970;Huskey and Griffin 1979). regA is a nuclear protein that is related to transcriptional repressors and expressed in somatic cells and required to maintain their fate Stark et al 2001). regA belongs to a family of VARL (Volvocine algae regA-like) proteins with 14 members in Volvox and 12 in Chlamydomonas (Duncan et al 2006(Duncan et al , 2007.…”
Section: Multicellular Innovations In the Volvocine Lineage Are Modifmentioning
confidence: 99%
“…To our knowledge, cis-acting elements located outside promoters, or 39 of the ORF affecting the expression of promoters have not previously been reported in yeast for Pol II promoters, though similar cis-acting elements have been described in yeast for Pol III transcribed genes and in other organisms, some localized inside introns (Errede et al 1987;Martin et al 2001;Stark et al 2001;Calderwood et al 2003;Delaloy et al 2008). In yeast, activators or repressors generally function when their corresponding cis-acting elements are located at distances no greater than 700 bp (Guarente and Hoar 1984;Struhl 1984;Keegan et al 1986) upstream of the start site of transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that the transcription of regA is regulated primarily by two enhancers and one silencer located in the introns (Stark et al, 2001). But there were also indications that regA might be regulated at the translational level.…”
Section: Introductionmentioning
confidence: 99%
“…Cells of the V. carteri strain 153-68, which carries non-revertible mutations in both the nitA and regA loci , were co-bombarded with pVcNR15 (Gruber et al, 1996) and various regA constructs that were described before. Integration of regA constructs after transformation was tested by PCR as described by Stark et al (Stark et al, 2001). …”
Section: Volvox Strains Cultivation Conditions and Nuclear Transformmentioning
confidence: 99%
See 1 more Smart Citation